The Korean Wave as the Globalization of South Korean Culture - Victor Glodev; Gustaf Wijaya; Rachmah Ida (Universitas Prof. Dr. Moestopo (Beragama), 2023)
The purpose of this study is to trace the growing attractiveness of the Korean Wave to understand the domestic culture of Korea that is becoming a global trend. The study is focused on the factors facilitating the formation of the phenomenon and proves that this trend has become one of the country's main export commodities and a “soft power”, as the promotion of Korean culture is a matter of national importance and pride for Seoul. The Republic of Korea has been absorbing the elements of Western culture and transforming them into a new phenomenon, representing a kind of coexistence and crossbreeding of the Western lifestyle and the traditional Eastern values. The context for the study is the cultural homogenization of the West and the East. Is it a blessing or an evil? What are its challenges and achievements, advantages, and disadvantages? What are the reasons for South Korean cultural expansion? The method utilized in the research is narrative analysis to provide an overview of Korean pop culture that has been able to connect Western and Asian values into something unique.